PERAN PEREMPUAN DALAM KAJIAN KOMUNIKASI POLITIK DAN GENDER DIKAJI DALAPERSPEKTIF HUKUM - KARMAN (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
Gender-based imbalance refers to imbalance in access to important resources such as power in material goods, services, prestige, roles, time, education and training and freedom from coercion or physical abuse. The concept of political communication aims to gain public support for a candidate or political policy. In the political realm, political communication is needed in order to get public support for a candidate or political policy. Women who play an active role in political parties or legislative institutions actually have the capacity as political communicators either individually or represent political institutions or organizations. In this role, women seek more direct forms of political participation in realizing political development. The representation of women in politics, especially in the people's representative institutions itself, is not without basic reasons. There are several things that make fulfilling the 30% quota for women's representation in politics important. Some of them are responsibility and sensitivity to public policy issues, especially those related to women and children, as well as the environment, good morals, women's ability to do multitasking work and manage time, and what is no less important is habitability and the fact that women has also carried out duties as a leader in social groups and in community activities, such as in posyandu, women's empowerment groups, school committees, and recitation groups.